Pengaruh Kultivar dan Waktu Panen Berbeda Hidroponik Fodder Sorgum terhadap KcBK dan KcBO - Asih Pujiastuti; Nor Goyatuh Khusnul Hitamy (Faculty of Animal Husbandry, University of Mataram, 2026)
Green fodder cultivated hydroponically is called hydroponic fodder. Hydroponics is one way of cultivating plants without soil media, especially those with limited land. This study aims to determine the effect of different cultivars and harvest times of sorghum hydroponic fodder in KcBK and KcBO. The study used a factorial Completely Randomized Design (CRD) with 2 treatments (sorghum cultivars and harvest time) and each treatment was repeated 3 times. The parameters observed were KcBK and KcBO. The data obtained were analyzed by analysis of variance. If there is interaction or influence between treatments, it will be tested further using the Duncan test. The results of the analysis of variance showed that harvest time had no effect on KcBK and KcBO, but the cultivar had a significant effect (P<0.05) on KcBK and KcBO. The conclusion of the study was that the A2B1 treatment showed the highest KcBK and KcBO values ​​compared to the A1B1 treatment.